Proximal stability assessment of knee osteoarthritis patients - Maryama AD Daud,; Nur Rasyiqah AR, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Proximal stability consists of core and hip stability play a significant role in supporting the body weight in stationary and in motion. Thus, proximal stability could contribute to knee osteoarthritis (OA). Therefore, this study was carried out to determine the core stability and hip stability of knee OA patients. A total of thirty-two women aged between 45 to 60 years had volunteered to participate in this study, comprised of 16 knee OA patients and 16 normal. Hip stability was assessed using hip crossover test and core stability was assessed using core muscle endurance, core muscle strength and core muscle flexibility. Data of hip stability, core muscle strength and flexibility were analyzed using chi-square; and core muscle endurance data were analyzed using independent sample t-test. Compared to normal subjects, knee OA patients have poor hip stability [Hip Crossover Test (λ=0.500, p=0.033)] and core stability. Core stability was assessed based on core muscle strength [abdominal muscles (χ=12.157, p<0.001); quadriceps and gluteal muscles (χ=13.364, p<0.001); hip muscles (χ=17.936, p<0.001); latissimus dorsi and quadriceps (χ=15.906, p<0.001)]; core muscle endurance [plank endurance (t=4.719, p<0.001); trunk flexion (t=2.824, p=0.008); trunk extension (t=1.364, p=0.193)]; core muscle flexibility [Ely’s test (λ=0.438, p=0.010)]. The proximal stability of knee OA patients appears to be significantly weaker than normal subjects. Thus, core stability and hip stability training have high potential not only to lessen the symptoms of knee osteoarthritis but to improve the functional movement of knee OA patients.